2023
DOI: 10.1073/pnas.2300839120
|View full text |Cite
|
Sign up to set email alerts
|

DNA methylation in the mouse cochlea promotes maturation of supporting cells and contributes to the failure of hair cell regeneration

Abstract: Mammalian hair cells do not functionally regenerate in adulthood but can regenerate at embryonic and neonatal stages in mice by direct transdifferentiation of neighboring supporting cells into new hair cells. Previous work showed loss of transdifferentiation potential of supporting cells is in part due to H3K4me1 enhancer decommissioning of the hair cell gene regulatory network during the first postnatal week. However, inhibiting this decommissioning only partially preserves transdifferentiation potential. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 75 publications
(101 reference statements)
0
1
0
Order By: Relevance
“…Previous studies have demonstrated that cochlear developmental genes, such as Atoh1, exhibit greater accessibility in HCs and SCs during P1 compared to P8 mice, which display more pronounced methylation in SCs and inhibit HC regeneration in P8 mice. [63] This may account for the reduced maturation of regenerated HCs following AAV-GPAS injection after P7, thereby impeding the restoration of auditory function after DTR injury. Despite the existence of various strategies to promote HC regeneration by multiple genes, [19,20,22] there remains a dearth of research on restoring hearing function through regenerative HCs in cases of HC damage.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that cochlear developmental genes, such as Atoh1, exhibit greater accessibility in HCs and SCs during P1 compared to P8 mice, which display more pronounced methylation in SCs and inhibit HC regeneration in P8 mice. [63] This may account for the reduced maturation of regenerated HCs following AAV-GPAS injection after P7, thereby impeding the restoration of auditory function after DTR injury. Despite the existence of various strategies to promote HC regeneration by multiple genes, [19,20,22] there remains a dearth of research on restoring hearing function through regenerative HCs in cases of HC damage.…”
Section: Discussionmentioning
confidence: 99%
“…Researchers are exploring compounds to regulate epigenetic modification as a potential avenue for alleviating acquired hearing loss. Epigenetic regulation is also crucial for inner ear HC regeneration, which offers an opportunity for hearing loss therapy [69,70].…”
Section: Molecular Genetics and Epigeneticsmentioning
confidence: 99%